Growth and biomass of Wolffia arrhiza with different sources of organic fertilizer - Bahagia, Bahagia; Erlangga, Erlangga; Rusydi, Rachmawati; Ayuzar, Eva; Khalil, Munawwar; Hartami, Prama (Acta Aquatica: Aquatic Sciences Journal, 2024)
Wolffia arrhiza has a growth rate and biomass as well as a good nutritional content for the growth of cultivated fish, especially herbivorous fish. Due to the high protein content (up to 45% of the dry weight), Wolffia is an excellent plant for the production of various biologically active substances, especially proteins. These plants can double every 1-6 days, similar to algae or mushrooms, and the number of leaves doubles every 2-3 days. This study aims to determine the effect of different fertilizer sources on doubling time, relative growth rate, population density and biomass of Wolffia arrhiza and water quality. The method used in this research is experimental. The research design used a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatments were as follows: treatment A: chicken manure, B: cow manure, C: buffalo manure and D: goat manure with each dose of 200 grams. Parameters observed included doubling time, relative growth rate, population density, biomass and water quality parameters. The results showed that treatment B (cow manure) gave the highest value for doubling time, 1.59 days, relative growth rate 0.392 g/day, population density 209.75 ind/cm2, biomass 94.97. Keyword: Biomass; Fertilizer; Growth; Wolffia